EVALUATION OF THE EFFICIENCY OF EPIDEMIOLOGICAL SURVEILLANCE OF DENGUE HEMORRHAGIC FEVER (DHF) IN INDONESIA FOR THE 2018-2023 PERIOD - Hana, Adelfina Maretti; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Dengue hemorrhagic fever transmitted through the Aedes aegypti mosquito vector is still an important health problem in the world. Particularly in Indonesia, dengue hemorrhagic fever was first recognized in 1968 in DKI Jakarta and Surabaya and continued to spread to thirty-three provinces in Indonesia. The epidemiologic pattern of dengue infection changes from year to year, with the number of cases peaking every 10-year cycle. Epidemiological surveillance is a very important activity in supporting the control and management of infectious diseases, including dengue control and management activities. The purpose of this study was to determine how to evaluate the efficiency of epidemiological surveillance of dengue hemorrhagic fever. This research uses the literature study method. The results obtained from several studies related to the relationship between the effectiveness of the implementation of epidemiological monitoring and the reduction in the number of DHF cases. The relationship between data collection and the quality of surveillance implementation. And evaluation of the existing dengue surveillance system in Indonesia. There is a strong correlation between good monitoring and case reduction, as well as a close relationship between accurate data collection and the quality of surveillance implementation. The evaluation of the surveillance system in Indonesia revealed challenges that must be overcome to improve efficiency and effectiveness in addressing the risk of DHF. Sustainable and holistic solutions are needed to strengthen the infrastructure and capacity of Indonesia's dengue epidemiological surveillance system. Keywords: Dengue hemorrhagic fever, epidemiology, surveillance